Macroeconomic Variables Effect on 10-Year Tenor Government Bonds Yield - Sihombing, Pardomuan; Edi Santoso; Dini Hariyanti (SAN Scientific, 2023)
This study aims to analyze the effect of macroeconomic conditions on the yield of 10-year government bonds. The macroeconomic indicators studied were the consumer price index, BI 7 days reverse repo rate, foreign exchange reserves, Indo CDS 5 years, and the Government Budget Deficit from January 2009 to December 2019. This research uses the Vector Error Correction Model (VECM) method because there is cointegration between variables, indicated by Trace Statistics and Max-Eigenvalue statistics, which are greater than Critical Value. The analysis results show that the Consumer Price Index (CPI) and the Government Budget Deficit positively influence the 10-year tenor government bond yield. In contrast, the 5-year Indo CDS, BI 7 days reverse repo rate, and Foreign Exchange Reserves negatively affect the 10-tenor government bond yield year. The policy implications for the yield of 10-year government bonds can be beneficial and useful for the government as the economic authority in issuing bonds, the regulator (Bank Indonesia), and helping investors to develop investment strategies in government bonds by continuously monitoring and predicting the direction of movement of these variables so that they can creating an optimal portfolio of government bonds.